PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING(CTL) UNTUK MENINGKATKAN RETENSI SISWA DALAM PEMBELAJARAN IPA KELAS V SDN 130 PEKANBARU - Hendri Marhadi; Syahrilfuddin; Liyaumi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2013)
The research aimed to examine the effect of the Contextual Teaching and Learning (CTL) model on improving students’ retention in science learning. Contextual Teaching and Learning (CTL) is a learning concept that helps teachers connect learning materials with real-life situations, enabling students to relate knowledge to their everyday experiences. The CTL model emphasizes the presentation of real and meaningful contexts in the classroom. Retention refers to students’ ability to store and recall information after the learning process has taken place. This research employed a one-group pretest–posttest design to analyze the data. A retention test (retest) was administered twelve weeks after the posttest to measure students’ retention. The results showed that the Contextual Teaching and Learning (CTL) model had a significant effect on students’ retention in science learning among fifth-grade students at SDN 130 Pekanbaru City. The mean score of students’ retention in this study reached 130%, which was categorized as “very good.” Furthermore, the findings indicate that the Contextual Teaching and Learning (CTL) model dominantly influences students’ memory and retention in science learning.